ERMes: Open Source Simplicity for Your E-Resource Management - Chilton, Galadriel; Doering, William (My University, 2009)
The article presents update on the use of electronic resource management systems (ERM) in libraries. It highlights the functionality of ERMes, which is a relational database that supports systems and communication venues. Among the proposed enhancements to ERMes being investigated are the addition of workflow checklists, data fields for distributor information, account/invoice numbers, database description, and creation of a Web overlay. Also presented are feedback from librarians and electronic resource coordinator on the implementation of ERMes.
Keywords: Workflow; Databases; Relational databases; Electronic records; ERMs; Electronic resource management; Management